Organising Freedom : Nordic Art of the '90s - Elliott, David; Levin, Kim; Poshyananda, Apinan; Birnbaum, Danïel; Abildgaard, Dorthe; Haapala, Leevi; Runólfsson, Halldór Björn; Eiebakke, Anders; Stjernstedt, Mats; Moderna museet, Stockholm (Stockholm : Moderna Museet Stockholm, 2000)
Ahtila, Eija-Liisa ; Bäckström, Miriam ; Eliasson, Olafur ; Eriksson, Annika ; Friberg, Maria ; Gamdrup, Mads ; Haaning, Jens ; von Hausswolff, Carl Michael ; Hedlund, Maria ; Hakansson, Henrik ; Karlsson Rixon, Annica ; Koester, Joachim ; Kolding, Jakob ; et al.
Moderna Museet, Stockholm, 2000.
kunstcatalogus
Keywords: Scandinavië